Multicultural-Based Islamic Religious Education Learning Design in Indonesia - Saharuddin, Munawir; St Wardah Hanafie Das (PT. Islamic Research Publisher, 2024)
Multicultural-based Islamic Religious Education (PAI) in Indonesia has an important role in building a harmonious and tolerant society. This study aims to formulate Islamic Religious Education learning design that integrates diversity values into the curriculum, teaching methods, and evaluation. Through a qualitative and descriptive approach, this study collected data from various literature sources, including relevant journals and books. The results showed that PAI curriculum design should include clear learning objectives, relevant materials, and interactive and participatory teaching methods. In addition, collaboration between educational institutions, teachers and the community is essential in implementing this curriculum. Learning evaluation should also include aspects of students' knowledge, attitudes, and skills in interacting with diversity. Thus, education can act as a tool to create peace and mutual respect among various groups of society. This research is expected to contribute to the development of religious education that is more inclusive and responsive to diversity in Indonesia.